Exploring the Side Effects of GLP-1 Receptor Agonist: To Ensure Its Optimal Positioning - Jung A Kim; Hye Jin Yoo (Diabetes & Metabolism Journal)
Although glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have demonstrated considerable efficacy in the treatment of diabetes and obesity, it is essential to recognize that their use is associated with certain intrinsic risks that must not be disregarded. The incidence of adverse effects, particularly gastrointestinal complications, psychiatric disorders, and ocular problems, highlights the critical need for thorough patient assessment and continuous monitoring to ensure both the safety and effectiveness of treatment. Despite the possibility of adverse events, GLP-1 RAs continue to represent a crucial therapeutic modality for metabolic disturbances. This highlights the significance of ongoing research initiatives aimed at optimizing their safe utilization and refining current treatment protocols to improve patient outcomes. This review summarizes updated research findings regarding the adverse effects of GLP-1 RAs, their mechanisms of action, and guidelines for clinical application.